Effect of Social Interaction and Gamer-Game Relationships on Mobile Legends Gamer Retention in Indonesia: Experimental Study - Mohamamd Rifkiana; Devi Ajeng Efrilianda (Universitas Negeri Semarang, 2024)
Indonesia has the most internet users and gamers globally, and mobile video games are one of the biggest markets. One of the most popular game genres is multiplayer online battle arena (MOBA), such as Mobile Legends: Bang Bang (MLBB). This study aims to determine the effect of social interaction network factors and gamer-game relationships on MLBB gamer retention. The research model used combines three theories: social capital theory, social presence theory, and self-perception theory. Data was collected using the inverse square root technique. A total of 211 questionnaire data were analyzed using a partial least squares-structural equation model (PLS-SEM) with the help of the SmartPLS 4 tool. The results showed that all social interaction network variables and gamer-game relationships were positively related to the sense of community (SC), relationship switching cost (RCS), and gaming habit (GH), which in turn were positively related to gamer retention (RG). However, the variables network convergence (NC) and relationship length (RL) have no relationship on all variables and thus do not affect gamer retention. The findings of this study suggest that social capital, social presence, and self-perception theory can prove and explain the relationship between social networks and gamers' relationship with games, which can effectively increase the retention of users, which in turn creates a competitive advantage for developers or publishers.